Strategi Optimalisasi Kemampuan Lahan dalam Penyediaan Air Tanah di Kota Balikpapan - Dwiana Novianti Tufail; Rahmayani (LPPM ITK, 2022)
The growth of Balikpapan City can be seen from the rapid development. The influence of land use change and reduced water catchment areas is one of the problems that occurs in Balikpapan City. It is known that the area of forest land use in 2014 was 22,856.95 ha, while in 2018 the area of forest land use decreased to 18,418.76 ha. This study aims to analyze the level of land capability groundwater supply and determine strategies for optimizing groundwater supply land capabilities in Balikpapan City. Based on the results, ability of land in providing groundwater in Balikpapan City is divided into 4 classifications. The strategy of optimizing land capabilities providing groundwater in Balikpapan Utara is the application infiltration wells to improve groundwater conditions and maintain the stability of high groundwater levels. In Balikpapan Selatan, Balikpapan Tengah and Balikpapan Kota, additional infiltration capabilities are carried out such as the creation of Biopori Infiltration Holes (LRB) and Biopori Infiltration Channels (SPB), in Balikpapan Timur strategies are environmental pollution control and groundwater quality management, while in Balikpapan Barat, the strategies is maintain land capabilities maintaining the quality of water and controlling the conversion forest functions into built-up land.